Scientific collaboration of Library & Information Science research in China (2012-2013) - Jabeen, Munazza; Imran, Muhammad; Badar, Kamal; Rafiq, Muhammad; Jabeen, Misbah; Yun, Liu (Malaysian Journal of Library and Information Science, 2017)
The present study is the first of its kind as it attempts to ascertain the current status of library and information science (LIS) research from the Chinese perspective, by focusing on English research contributions by Chinese LIS scholars. Leading contributors; individual (author) contributors; institutional contributors, and research collaborations were examined. The review comprises 564 articles published in international journals indexed by Social Science Citation Index (SSCI) from 2012-2013. Co-authorship analysis and co-citation analysis were used to draw the results. The results revealed two major findings; first, the Chinese research community is engaged in focusing on cross-national collaboration to establish their existence in international literature and establish colleague relationship with foreigner researchers. USA, UK, and Belgium are the primary counterparts of international collaborative papers. Chinese institutions have eminent professors in the LIS field who incorporate international-oriented scholarly researches (48.04%) around the globe. Secondly, Chinese researchers have enough knowledge to conduct research, both as single authors (26.24%) and through internal academic collaboration between senior and junior researchers. The Chinese LIS research community has not paid much attention to conducting research on inter-institutional level (7.20%) and on inter-regional level (6.73%). Nevertheless, Wuhan University, City University Hong Kong, and Chinese Academy of Sciences have emerged as the leading institutions in producing LIS publications. Chinese immigrant scholars also have contributed to LIS China’s international scientific collaboration. It is a worthwhile and unique study as it examines the collaboration trends networks analysis of international publications by Chinese scholars